MENINGKATKAN MINATaDAN HASIL BELAJAR SISWA MELALUI METODE DEMONSTRASI DENGAN PEMANFAATAN BAHAN LIMBAH PLASTIK DI KELAS VII.3 SMP PEMBANGUNAN LABOR UNP - Vovvy Z, Dra. Zubaidah, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this study was to increase students interest and learning outcomes through  demonstration methods with the use of plastic waste materials in class VII.3 of the UNP Labor Development Middle School. This type of research is classroom action research. The results showed that student learning outcomes increased from pre-cycle to cycle I and increased from cycle I to cycle II. The percentage in the pre cycle was 3.7% because only 1 student achieved complete grades. In the first cycle students who completed increased to 10 with the percentage of students 37% and in the second cycle students who completed increased significantly to 23 with the percentage of students 85.2%.Keywords: Interest; Learning outcomes; Demonstration method; Waste material